Electric discharge synthesis of nickel nanoparticles with virtual instrument control. Issue 5 (3rd September 2021) - Ramos, Rogelio; Valdez, Benjamin; Nedev, Nicola; Curiel, Mario; Perez, Oscar; Salvador, Jorge
Abstract: Colloidal nickel nanoparticles were prepared by a top-down approach using an electric discharge. The method was improved by a computerized control unit implemented with virtual instrumentation. A controlled electric arc discharge between two nickel electrodes generates a plasma, which rapidly disintegrates the nickel to form nanoparticles in deionized water. Dynamic light scattering and scanning electron microscopy show synthesis of nickel nanoparticles with size distributions that depend on the discharge parameters.